Magical Props: The Cinematic Object and Narrative Magic in Poetic Realist, Surrealist and Magical Realist Film - Stollman, Sarah Ellen (Curtin University, 2023)
This thesis identifies a magical narrative function of certain cinematic objects found in the film modes of poetic realism, surrealism, and magical realism, as analysed in the films Incendies, Little Otik and Amélie. This narrative magic is enabled by the prop’s agential transformation through a portrayal of sensorial qualities within the frame. The thesis argues that the cinematic magical object operates to drive character, action and plot and to reveal theme within the story world.